A bird's eye view of a deleterious recessive allele. (July 2016) - Ekblom, Robert
Abstract : In the endangered Scottish chough ( Pyrrhocorax pyrrhocorax ) population, a lethal blindness syndrome is found to be caused by a deleterious recessive allele. Photo: Gordon Yates. In Focus: Trask, A.E., Bignal, E.M., McCracken, D.I., Monaghan, P., Piertney, S.B. & Reid, J.M. (2016) Evidence of the phenotypic expression of a lethal recessive allele under inbreeding in a wild population of conservation concern. Journal of Animal Ecology, 85, 879–891. In this issue of Journal of Animal Ecology, Trask et al . (2016 ) report on a strange, lethal, blindness that regularly affects chicks of an endangered bird population. The authors show that the inheritance mode of this blindness disease precisely matches the expectations of a recessive deleterious mutation. Intriguingly, there is also an indication that the disease‐causing variant might be maintained in the population by balancing selection, due to a selective advantage for heterozygotes. Could this finding have consequences for conservation actions implemented for the population? Abstract : In the endangered Scottish chough ( Pyrrhocorax pyrrhocorax ) population, a lethal blindness syndrome is found to be caused by a deleterious recessive allele. Photo: Gordon Yates.